Silo-Guard for corn silage - K. Bolsen; H. Ilg (Kansas Agricultural Experiment Station Research Reports, 1980)
Two corn silages (34 to 36% DM) were made August 4 and 5, 1976; one was ensiled without additive (control), the other with Silo-Guard added at 1.5 lbs. per ton of fresh crop. Silos were opened after 68 days, and each silage was full-fed to 15 yearling steers (3 pens of 5 steers) during a 91-day trial (October 12, 1976, to January 11, 1977). Complete-mixed rations contained 84% silage and 16% soybean meal supplement on a DM basis.
Keywords: Cattlemen& #x27; s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Silo-Guard; Rations; Corn silage